Persepsi Mahasiswa Kota Palembang terhadap Fenomena Childfree - Nina Damayati; Monanisa Monanisa; Heri Setianto; Deni Puji Hartono (Universitas Batanghari Jambi, 2026)
This study aims to analyze the perceptions of university students in Palembang City toward the childfree phenomenon and to identify the factors influencing the formation of these perceptions. The study employed a descriptive qualitative approach involving eight university students from various higher education institutions in Palembang City. Participants were selected through purposive and snowball sampling techniques. Data were collected through in-depth interviews and analyzed using the interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the majority of students perceive childfree as a personal right and individual choice; however, they tend not to support its application in their own lives. These perceptions are influenced by cultural and religious values, family expectations, and exposure to information through social media. Although economic considerations and mental readiness are viewed as rational reasons for supporting the childfree choice, strong social norms remain the primary consideration in reproductive decision-making. The findings further reveal that the childfree phenomenon in Palembang City has developed more as a social discourse than as a widespread practice, and therefore has not yet had a significant impact on local demographic dynamics. This study highlights an ongoing process of value negotiation between modernity and tradition in shaping the reproductive preferences of the younger generation.